Conventional Contrast Study in Demonstration of Branchial Cleft Fistula: A Report of Three Cases with Review of the Literatures. - Boonjunwetwat, Darunee; Stapatayawong, Varunee (The ASEAN Journal of Radiology, 2023)
Anomalies of the branchial apparatus are one of the common benign congenital neck mass. We have reported three cases of the branchial cleft fistula. One is the anomaly of the second branchial cleft and the other two cases are the anomaly of the third ones. Clinical presentations, rediographic contrast studies, revisions of the anatomy, embryology and differential diagnosis of the mass are included.